Tuberculoma With Visual and Vestibular Symptoms in A β-Thalassemia Patient: A Case Report - Suryawijaya, Evlyne Erlyana; Ariarini, Ni Nengah Rida; Diafiri, Dinda; Dewati, Eva; Sitorus, Freddy (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which can affect the lungs (pulmonary TB) as well as other organs (extrapulmonary TB), including the central nervous system (CNS). The number of TB cases in Indonesia remains high, with 969,000 cases reported in 2021. Tuberculoma is a manifestation of TB in the CNS, presenting as an intracranial mass due to the spread of TB from other organs. It is a rare and serious form of CNS TB infection. The presence of congenital β-thalassemia adds complexity to the pathogenesis, diagnosis, and treatment of tuberculoma. Case Description: A 25-year-old female with a history of β-thalassemia HbE intermedia with a major phenotype presented with the main complaint of blurred vision in the lower right visual field. The patient also experienced vertigo, headache, and a history of seizures. Examination revealed inferior right quadrantanopia, anemia, leukopenia, and thrombocytopenia. Imaging and CSF analysis supported a diagnosis of intracranial tuberculoma. The patient was treated with anti-TB medication and intravenous dexamethasone. Discussion: Patients with thalassemia may have an increased risk of TB infection, including CNS TB. Tuberculoma involves granuloma formation in the brain, often in the meninges and cerebrum. Its manifestations vary and can include headaches and seizures. Diagnosis is based on clinical history, radiological findings, and laboratory results. The patient’s symptoms and imaging findings supported a diagnosis of tuberculoma, for which anti-TB and neurorestorative therapy was administered. Conclusions: Tuberculoma, as a manifestation of CNS TB, presents with variable and non-specific symptoms. Visual field disturbances can be one of the presenting symptoms that aid in diagnosis. Clinical, radiological, and laboratory evaluations are necessary for prompt and accurate diagnosis. Treatment involves anti-TB therapy and dexamethasone. This case highlights the importance of early diagnosis and comprehensive management of complex extrapulmonary TB infections.